2008
DOI: 10.1785/0120070076
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Near-Field Ground Motion from Dynamic Earthquake Rupture Simulations

Abstract: This study investigates near-field ground-motion variability due to dynamic rupture models with heterogeneity in the initial shear stress. Ground velocity seismograms are synthesized by convolving the time histories of slip velocity obtained from spontaneous dynamic rupture models with Green's functions of the medium calculated with a discrete wavenumber/finite-element method. Peak ground velocity (PGV) estimated on the synthetics generally matches well with an empirically derived attenuation relation, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 49 publications
6
64
0
Order By: Relevance
“…At such short distance, the ground shaking was generally thought to be dominated by source rupture complexity (e.g. Ripperger et al 2008). Intraevent standard deviation estimates obtained in this study are in agreement with the work of and indicate that the PGV variability and the apparent attenuation induced by topography is always lower than those associated with velocity heterogeneity, although the difference reduces sensibly at very short distance (e.g.…”
Section: Discussion a N D C O N C L U S I O N Ssupporting
confidence: 87%
See 2 more Smart Citations
“…At such short distance, the ground shaking was generally thought to be dominated by source rupture complexity (e.g. Ripperger et al 2008). Intraevent standard deviation estimates obtained in this study are in agreement with the work of and indicate that the PGV variability and the apparent attenuation induced by topography is always lower than those associated with velocity heterogeneity, although the difference reduces sensibly at very short distance (e.g.…”
Section: Discussion a N D C O N C L U S I O N Ssupporting
confidence: 87%
“…However, we note that PGV variability values derived from combining topography and velocity perturbations are comparable with those derived from dynamic rupture simulations in the near-source region as obtained by Ripperger et al (2008) and from empirical ground-motion prediction equations (e.g. Abrahamson et al 2008).…”
Section: Discussion a N D C O N C L U S I O N Ssupporting
confidence: 76%
See 1 more Smart Citation
“…Finally, PGV is taken as the median value of all the 90 geometric means. Ripperger et al (2008) compared different PGV approximations from the two horizontal components and observed that GMRotD50 is a stable measure of the PGV showing a low dependence on the orientation of the horizontal components. Figure 6 shows the mean (with a standard deviation error bar) of ground motion in terms of natural log of PGV averaged over the different azimuths and along the R JB distances for the fault models considered in this study.…”
Section: Pgv Calculationmentioning
confidence: 99%
“…Therefore, the locally identified SMGAs may be different from the main rupture front or characterized by a larger stress drop. A more complicated 'inhomogeneous' fault model (e.g., Ripperger et al 2008) might be more appropriate in such cases. Stochastically heterogeneous models (e.g., Ide and Aochi 2005) should be used in future ground motion estimation studies.…”
Section: Resultsmentioning
confidence: 99%